THE INFLUENCE OF SHORT VIDEO MARKETING ACTIVITIES ON TIKTOK SHOP AND CUSTOMER EXPERIENCE ON CUSTOMER RELATIONSHIP QUALITY AND ITS IMPACT ON CUSTOMER LOYALTY IN THE FASHION INDUSTRY - Ritonga, Ray Handaya; Simbolon, Freddy Pandapotan (Ikatan Dosen Menulis, 2025)
This study aims to analyze the influence of short video marketing activities on TikTok and customer experience on customer relationship quality, as well as their impact on customer loyalty in the fashion industry on TikTok Shop. A quantitative approach was employed using a survey method involving 250 Gen Z respondents in Jakarta who actively shop for fashion products through TikTok Shop. Data were collected through questionnaires and analyzed using the Partial Least Squares Structural Equation Modeling (SEM-PLS) technique. The results show that short video marketing activities and customer experience have a positive and significant effect on customer relationship quality. Furthermore, customer relationship quality also has a significant effect on customer loyalty. In addition, short video marketing activities and customer experience were found to directly influence customer loyalty. These findings offer practical implications for fashion industry players in designing effective digital marketing strategies that focus on enhancing customer experience and relationships to foster long-term loyalty.